2014
DOI: 10.1016/j.pain.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Distinct brain mechanisms support spatial vs temporal filtering of nociceptive information

Abstract: The role of endogenous analgesic mechanisms has largely been viewed in the context of gain modulation during nociceptive processing. However, these analgesic mechanisms may play critical roles in the extraction and subsequent utilization of information related to spatial and temporal features of nociceptive input. To date, it remains unknown if spatial and temporal filtering of nociceptive information is supported by similar analgesic mechanisms. To address this question, human volunteers were recruited to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
117
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 43 publications
3
117
1
1
Order By: Relevance
“…Previous fMRI studies have shown that the Periaqueductal Gray (PAG) of the brainstem and Rostral Ventral Medulla (RVM) are activated by an OA‐paradigm, but not during standard CPM‐paradigms (Nahman‐Averbuch et al., ), suggesting that OA and CPM activate different pain inhibitory systems. Moreover, several studies demonstrated that the facilitatory influences on spinal nociception that are emanated from the RVM are partly mediating the central sensitization (Millan, , Vo and Drummond, ), while the possible role of a peripheral mechanism involved in OA could explain differences in brain activation during OA and CPM (Nahman‐Averbuch et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous fMRI studies have shown that the Periaqueductal Gray (PAG) of the brainstem and Rostral Ventral Medulla (RVM) are activated by an OA‐paradigm, but not during standard CPM‐paradigms (Nahman‐Averbuch et al., ), suggesting that OA and CPM activate different pain inhibitory systems. Moreover, several studies demonstrated that the facilitatory influences on spinal nociception that are emanated from the RVM are partly mediating the central sensitization (Millan, , Vo and Drummond, ), while the possible role of a peripheral mechanism involved in OA could explain differences in brain activation during OA and CPM (Nahman‐Averbuch et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…6,19,22,42 Indeed, several studies show that offset analgesia produces increased activity in the dorsolateral prefrontal cortex (DLPFC) and anterior insula, which mirrors the activity of brain regions activated in the modulation of pain by cognitive processes such as placebo, distraction, and meditation. Thus, Nahman-Averbuch and colleagues hypothesized that part of offset analgesia is mediated or amplified by cognitive processes associated to the prediction of the time course of pain.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Thus, Nahman-Averbuch and colleagues hypothesized that part of offset analgesia is mediated or amplified by cognitive processes associated to the prediction of the time course of pain. 19 Additional research suggests an integral role of the cerebellum in offset analgesia. 11 In particular, Ruscheweyh et al discovered reduced offset analgesia in patients with cerebellar infarction compared to sex- and age- matched controls.…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioned pain modulation (CPM) is a physiological phenomenon whereby pain evoked at one region of the body (e.g., foot) reduces pain perceived at another body location (e.g., hand) under healthy physiological conditions. CPM involves central nervous system processes at cortical, subcortical and brainstem levels [4]. This phenomenon is widely documented as being disrupted in patients with chronic pain, particularly patients with fibromyalgia, and is a primary indicator of dysregulated descending control of pain.…”
Section: Introductionmentioning
confidence: 99%